Clinical, Serological, Whole Genome Sequence Analyses to Confirm SARS-CoV-2 Reinfection in Patients From Mumbai, India - Shastri, Jayanthi; Parikh, Swapneil; Agrawal, Sachee; Chatterjee, Nirjhar; Pathak, Manish; Chaudhary, Sakshi; Sharma, Chetan; Kanakan, Akshay; A, Vivekanand; Srinivasa Vasudevan, Janani; Maurya, Ranjeet; Fatihi, Saman; et al. (Frontiers in Medicine, 2021)
Abstract: Background: SARS-CoV-2 infection may not provide long lasting post-infection immunity. While hundreds of reinfections have reported only a few have been confirmed. Whole genome sequencing (WGS) of the viral isolates from the different episodes is mandatory to establish reinfection. Methods Nasopharyngeal (NP), oropharyngeal (OP) and whole blood (WB) samples were collected from paired samples of four individuals who were suspected of SARS-CoV-2 reinfection based on distinct clinical episodes and RT-PCR tests. Details from their case record files and investigations were documented. RNA was extracted from the NP and OP samples and subjected to WGS, and the nucleotide and amino acid sequences were subjected to genome and protein-based functional annotation analyses. Serial serology was performed (Anti-NC IgG, Anti- S1 RBD IgG, sVNT). Findings In three patients the second episode had more symptoms, lower Ct values and longer duration of illness. Seroconversion was detected soon after the second episode in three patients. WGS generated a genome coverage ranging from 80.07% to 99.7%. Phylogenetic analysis revealed sequences belonged to G, GR and ‘Other’ clades. A total of 42 mutations were identified, consisting of 22 non-synonymous, 17 synonymous, two in upstream and one in downstream regions of the SARS-CoV-2 genome. Comparative genomic and protein-based annotation analyses revealed differences in the presence and absence of specific mutations in the virus sequences from the two episode in all four paired samples. Interpretation Genomic variations observed through whole genome sequencing supported by clinical presentation, molecular and serological tests, confirm four cases of reinfections of SARS-CoV-2. Funding Municipal Corporation of Greater Mumbai, ICGEB core funding, MLP-2005 and Fondation Botnar grants.